Forgotten People: Poverty, Risk and Social Security in Indonesia - . Nooteboom, G. (Power and Place in Southeast Asia, 2015)
In Forgotten People Gerben Nooteboom describes and analyses the livelihoods and social security of peasants and migrant Madurese. It offers a new way to categorise and analyse livelihood security of marginal people in Indonesia by using the concept of style.